Peranan Orang Tua Terhadap Kepercayaan Diri Anak dalam Meningkatkan Prestasi - Sukmayanti; Yustin, Jeremy; Ai, Salsa; Rahmadanti, Fira; Gusvina, Felisitas (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
This writing aims to fulfill the assignment for the Quatitative Research Methods course by investigating the role of parents in children’s self- confidence in increasing achievement. This research emphasizes how parental support, communication, and parenting style can shape children’s self confidences. As primary educators, parents have a great responbility to provide moral, emotional support and opportunities for childres to reach their own potential. Research shows that childres’s sel – confidence increases witf the right parenting approach and good examples from parents. This has a positive impact on the child’s academic performance. Strong self- confidence makes children brayer in facting difficulties and encouranges them to learn.